Freely Suspended, van der Waals Bound Organic Nanometer‐Thin Functional Films: Mechanical and Electronic Characterization. Issue 16 (4th March 2019) - Schaffroth, Lilian S.; Lenz, Jakob; Giegold, Veit; Kögl, Maximilian; Hartschuh, Achim; Weitz, R. Thomas
Abstract: Determining the electronic properties of nanoscopic, low‐dimensional materials free of external influences is key to the discovery and understanding of new physical phenomena. An example is the suspension of graphene, which has allowed access to their intrinsic charge transport properties. Furthermore, suspending thin films enables their application as membranes, sensors, or resonators, as has been explored extensively. While the suspension of covalently bound, electronically active thin films is well established, semiconducting thin films composed of functional molecules only held together by van der Waals interactions could only be studied supported by a substrate. In the present work, it is shown that by utilizing a surface‐crystallization method, electron conductive films with thicknesses of down to 6 nm and planar chiral optical activity can be freely suspended across several hundreds of nanometers. The suspended membranes exhibit a Young's modulus of 2–13 GPa and are electronically decoupled from the environment, as established by temperature‐dependent field‐effect transistor measurements. Abstract : Freestanding membranes composed of an electron‐conductive organic small‐molecular semiconductor are realized via a solution‐crystallization approach. Despite the comparably weak van der Waals force holding the small molecules together, the suspended films can be as thin as only 6 nm. The films show promising mechanical and semiconducting properties and optical planar chirality.